PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PADA RUMAH SAKIT PEMERINTAH DAN SWASTA DI KOTA PALEMBANG - Jusmawi Bustan (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2012)
The aims of this research is know the influence of service quality on patients satisfaction in government hospitals and private hospitals in the city of Palembang. The problems that exist in this study are: how much influence the quality of service simultaneously or partial satisfaction of patients in government and private hospitals in the city Palembang. Then, there a difference in patient satisfaction levels of government and private hospitals in the city of Palembang. Whether patients' expectations of government and private hospitals has been improved. Sampling techniques use in this research by way of non-probability purposive random sampling with the withdrawal of quota sampling method and selected purposively. Variables in the study is service quality as independent variables and patient satisfaction as dependent variable.Data analysis technique used is important performance analysis (IPA) and simple regression analysis. Based on the calculation results obtained the following conclusions: First, The simultaneous and partial service quality has influence on patient satisfaction in Government and Private Hospitals in the city of Palembang by 13,2 %, Second, in general the data show the results of research through descriptive methods importance performance analysis there was no difference between the level of patient satisfaction with the government hospital private hospital in the city of Palembang. All three of the results of data analysis with descriptive methods analisys performance importance of patient satisfaction (expectations) at the government hospital and private hospital is not exact. This is evident from the average total grand mean that is negative.